Understanding the Hadith of al-Laghwu during Friday Prayers - Prayitno, Doni; Muhajirin, Muhajirin; Zulfikar, Eko (JIA (Jurnal Ilmu Agama), 2024)
This article aims to find out the meaning of the al-Laghwu hadith during Friday prayers. This is motivated by the fact that in current conditions many Friday prayer congregations carry out activities during the sermon which could be said to fall into the al-Laghwu category. By using descriptive-analytical qualitative methods and a ma'ani al-hadith science approach, this article concludes that the meaning of al-Laghwu in the Prophet's hadith is a futile act that can reduce the reward and perfection or primacy of Friday prayers. The meaning of al-Laghwu is not only limited to the text of the hadith, namely speaking or admonishing others to be silent when the preacher is delivering his sermon. In the current context, the meaning of al-Laghwu can also be interpreted as sleeping during the sermon, playing on mobile phones such as WhatsApp, Instagram, Facebook, Twitter, YouTube, TikTok, games and similar activities, and distributing charity boxes. These actions cause the congregation to lose focus in listening to the sermon delivered by the preacher and also disturb other congregation members. Even though it is included in the al-Laghwu category and reduces the reward and perfection of Friday prayers, the Friday prayers performed are still considered valid.